Educating Bela Negara as Strengthening Element in Indonesia’s Strategy of Main Island Defense Implementation - Risman, Helda; Andayani, Lily; Timur, F. G. Cempaka; Akmalina, Aulia (International Journal of Demos (IJD), 2025)
Abstract This study examines how Bela Negara Education improves Indonesia's main islands' asymmetric defensive strategy. Our narrative assessment identifies effective and contextually acceptable state military education programs that match the topography of these important islands. The main island’s defense plan (P3B) implements the comprehensive defense strategy by designating the main islands as defensive bases from outer to inner mandala. Bela Negara Education is vital to public knowledge and active participation in the defense system. The 3CS Bela Negara Education program has promoted Bela Negara values and attitudes. Bela Negara Education should be based on five values: patriotism, sacrifice, nation-state consciousness, Pancasila as the guiding ideology, and Bela Negara capability development. This schooling should use four learning paths. This study advocates a welfare-first approach before teaching national values and developing stakeholder synergy for Bela Negara Education. Keywords: Asymmetric Threats, Defense Strategy, Main islands, National Sovereignty, Bela Negara Education, Total Defense System